2019
DOI: 10.1021/acsomega.8b02752
|View full text |Cite
|
Sign up to set email alerts
|

Capping Structure of Ligand–Cysteine on CdSe Magic-Sized Clusters

Abstract: Ligand molecules capping on clusters largely affect the formation and stabilization mechanism and the property of clusters. In semiconductor CdSe clusters, cysteine is used as one of the ligands and allows the formation of ultrastable (CdSe) 34 magic-sized clusters. Cysteine has sulfhydryl, amine, and carboxylate groups, all of which have coordination ability to the CdSe surface, and the bonding states of the three functional groups of ligand–cysteine on the CdSe core have not been deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…Some investigations of Cys binding modes on the surface of Cd-based clusters and nanoparticles have been previously reported. For example, by performing multinuclear ( 1 H, 13 C, 77 Se, 15 N, 113 Cd, and 23 Na) solid-state NMR techniques, Takegoshi et al have shown that the Cys ligand binds with CdSe 34 magic clusters via coordination to Cd 2+ ions as S – –NH 2 bidentate and S – monodentate ligand, in amounts of 43% and 57%, respectively. In another study using 13 C solid-state NMR, it was demonstrated that Cys binds to the surface of 2.9 nm CdSe QDs as a S – –COO – bidentate ligand. Density functional theory (DFT) calculations revealed that the interaction patterns between Cys and (CdSe) n vary with the cluster size and medium.…”
Section: Resultsmentioning
confidence: 99%
“…Some investigations of Cys binding modes on the surface of Cd-based clusters and nanoparticles have been previously reported. For example, by performing multinuclear ( 1 H, 13 C, 77 Se, 15 N, 113 Cd, and 23 Na) solid-state NMR techniques, Takegoshi et al have shown that the Cys ligand binds with CdSe 34 magic clusters via coordination to Cd 2+ ions as S – –NH 2 bidentate and S – monodentate ligand, in amounts of 43% and 57%, respectively. In another study using 13 C solid-state NMR, it was demonstrated that Cys binds to the surface of 2.9 nm CdSe QDs as a S – –COO – bidentate ligand. Density functional theory (DFT) calculations revealed that the interaction patterns between Cys and (CdSe) n vary with the cluster size and medium.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the elements found in main group inorganic semiconductors have NMR active nuclei, potentially making solid-state NMR an ideal tool for probing the structure of NPs. Solid-state NMR has previously been applied to a number of different NP systems, such as cadmium chalcogenides (CdX, X = S, Se, Te), [26][27][28][29][30][31][32][33][34] indium phosphide (InP), [35][36][37] silicon (Si), [38][39][40][41][42] etc., [43][44][45][46] to determine both the surface and bulk structure. Direct excitation solid-state NMR experiments mainly probe the bulk of the NPs, although surface NMR signals are visible in small diameter NP NMR spectra.…”
Section: Introductionmentioning
confidence: 99%
“…l -Cysteine, with sulfhydryl and carboxylate functional groups, facilitates the binding of CdSe/CdS DIRs to WSe 2 (as shown in Figure S5). , The TEM image of the mixture (Figure d) confirms that CdSe/CdS DIRs are indeed in contact with WSe 2 NSs.…”
Section: Results and Discussionmentioning
confidence: 61%